Effects of perfluoroalkyl substances on root and rhizosphere bacteria: Phytotoxicity, phyto-microbial remediation, risk assessment. (February 2022) - Liu, Huinian; Hu, Wenli; Li, Xin; Hu, Fangwen; Liu, Yanfen; Xie, Tanghuan; Liu, Bo; Xi, Yanni; Su, Zhu; Zhang, Chang
Abstract: Background: Per- and polyfluoroalkyl substances (PFAS) is easily sink into soil, affecting plants growth and microenvironment. However, the impacts of PFAS-related risk assessment on root and rhizosphere microbiomes are still poorly understood. Objective: Researched on Arabidopsis thaliana and Nicotiana benthamiana growing in contaminated with perfluorooctanoic acid (PFOA), hexafluoropropylene oxide-dimer acid (HFPO-DA) and their mixtures. Results: (i) Bioaccumulation of PFAS in roots was positively correlated with carbon chain length, contamination levels and exposure time, the phytotoxicity was as follows: HFPO-DA < (PFOA + HFPO-DA) < PFOA; (ii) Both short-term and long-term accumulation of PFAS would affect the changes in root antioxidant system and physiological metabolism; (iii) Single or mixed contamination of PFAS had unique influences on rhizosphere microbial diversity, community composition and interspecies interaction, and mixture was more complex. More importantly, the performance of Sphingomonadaceae and Rhizobiaceae microbial communities could contribute to the practice of phyto-microbial soil remediation. Future direction: Pay more attention on novel pollution pathway in cultivation, exposure levels for different plants (especially crops), as well as more exact and scientific risk assessments. Establish a new PFAS grouping strategy and ecotoxicity life cycle assessment framework. Graphical abstract: Image 1 Highlights: PFAS toxicity was related with carbon chain length, pollution level and exposure time. PFAS caused disturbances in the antioxidant system of plant-root. PFAS contamination affected plant-root microbiomes diversity and structure. Phyto-microbial joint remediation of PFAS contaminated soil was promising. Crop risk assessment for PFAS contamination in China was poorly developed.